Population study of Peristylus goodyeroides (Orchidaceae) in five habitats and implication for its conservation - SITI NURFADILAH (Biodiversitas Journal of Biological Diversity, 2017)
Nurfadilah S. 2017. Population study of Peristylus goodyeroides (Orchidaceae) in five habitats and implication for its conservation. Biodiversitas 18: 1084-1091. Many orchids have experienced population decline because of natural and anthropogenic disturbances and the remaining populations occur in fragmented habitats. The present study aimed to investigate (i) population of a terrestrial orchid, Peristylus goodyeroides (D. Don) Lindl., in terms of its demography, population size, and plant size, and (ii) characteristics of vegetation surrounding P. goodyeroides and its effect on the population size of P. goodyeroides (iii) environmental factors (litter thickness and soil pH) and their effects on the plant size of P. goodyeroides in five habitats. Number of individuals, plant height and leaf area of P. goodyeroides, surrounding vegetation, litter thickness, and soil pH were recorded in each habitat. The results showed that there was variation in the demographic structure of the population of P. goodyeroides in five habitats. Furthermore, three habitats of P. goodyeroides had small population size and small plant size compared to the other two habitats that had relatively larger population size and plant size. Small population size was correlated with taller vegetation surrounding P. goodyeroides reducing light availability for P. goodyeroides, while small plant size was related to sparse and thin litter cover causing low soil moisture and lacking nutrient availability for P. goodyeroides. Soil pH between habitats was similar and did not affect P. Goodyeroides plant size. The present study has implication on the conservation of P. goodyeroides for the improvement of population performance for the increase in population size and plant size for the species survival.